Tingkat Kedinamisan Kelompok Wanita Tani dan Hubungannya dengan Partisipasi dalam Program Pekarangan Pangan Lestari (P2L) di Kelurahan Sako dan Kelurahan Sukamulya Kota Palembang: The Dynamic Level of Women Farmer Groups and Its Relationship with Participation in Pekarangan Pangan Lestari Program (P2L) in Sako District and Sukamulya District Palembang City - Wulandari, Desi; oktarina, selly (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2025)
Pekarangan Pangan Lestari Program (P2L) is an activity carried out by community groups in an effort Pekarangan Pangan Lestari to increase food availability for households. The objectives of this research were (1) Measured the level of dynamism of women farmer groups in Pekarangan Pangan Lestari (P2L) program, (2) Measured the level of participation of women farmers in Pekarangan Pangan Lestari (P2L) program, and (3) Analyzed the relationship between the level of group dynamism and the participation of women farmers in Pekarangan Pangan Lestari (P2L) program. This research was carried out in Sako District and Sukamulya District, Palembang City in November 2023 – December 2023. The research method used was the survey method and census method. The data used was primary data and secondary data. Data analyzed used was a likert scale and spearman rank. The results of this research were (1) The level of dynamism of women farmer groups in Pekarangan Pangan Lestari program was classified as high or already dynamic. (2) The level of participation of women farmer group in Pekarangan Pangan Lestari Program in Sako District and Sukamulya District, Palembang City was classified as medium, and (3) The results of the rank-spearman test show that there was a significant relationship between the level of group dynamism and the participation of women farmers in Pekarangan Pangan Lestari program in Sako District and Sukamulya District with a moderate level of correlation, namely 0.471.